Green total factor productivity of dairy cows in China: essential facts from the perspective of regional heterogeneity - Guo, Jinguang; Fu, Yu (Frontiers in Environmental Science, 2023)
Enhancing the green total factor productivity of dairy cows (GPDC) is crucial for fostering the low-carbon sustainable development of dairy industry. This research utilizes the MinDW-MML index to examine the green total factor productivity of dairy cows using the unbalanced panel data of dairy cow in 26 provinces of China from 2004 to 2020, taking into account regional heterogeneity and unexpected output. The findings reveal that: (1) From 2004 to 2020, China's GPDC displayed a fluctuating and declining trend, with the steepest decrease occurring from 2007 to 2010 (2.26 percent at the common frontier and 1.81 percent at the group frontier). The fundamental cause of the low GPDC, as seen from the standpoint of efficiency decomposition, is technical advancement (technological change, or TC). (2) With respect to the two-level frontier, the GPDC exhibits a declining trend from east to west to central China. The eastern region benefits clearly from technological advancement (TC) and improved technical performance (EC), while the middle and western regions are mostly constrained by TC. (3) The GPDC displayed regional heterogeneity at several scales. While the efficiency values of medium- and small-scale aquaculture were low and large-scale aquaculture GPDC in the eastern and western regions was greater than 1, GPDC did not reach the effective state in the central region. On the basis of the foregoing results, the corresponding comments and suggestions are next offered.